Analisis Efektivitas Kebijakan Pemutihan Pajak Kendaraan Bermotor Pada Kepatuhan Wajib Pajak di Provinsi Jawa Barat - Yuli Dewi Lestari; Dian Anita (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
In the context of local government in Indonesia, one of the main challenges is to increase local own-source revenue (PAD), which is an indicator of the economic independence of a region. One important component of PAD is local taxes, including vehicle taxes. However, the level of taxpayer compliance is still low, with a decline in tax payments in 2020 affecting tax revenue and hampering regional development. The step taken by the local government is to provide tax incentives through the tax write-off policy program. When this policy was enacted, there was a short-term increase in tax revenue, but there was a perception among taxpayers that tax penalties could be waived periodically, which encouraged the postponement of future tax payments and triggered non-compliance. This study aims to determine the effectiveness of motor vehicle tax write-off in increasing taxpayer compliance in its implementation, how this policy affects taxpayer perceptions and whether this policy has a sustainable impact. The method used is a qualitative approach. The results show that most taxpayers feel helped, but there are those who see tax write-off as an opportunity to delay payment. This policy is effective in increasing short-term revenue, but has not fully increased awareness to pay taxes in a disciplined manner without incentives. It has a positive impact on PAD in a certain period, but does not permanently improve tax compliance.